ANALYSIS OF SPEED, PRESSURE AND DISTRIBUTION TEMPERATURE IN GAS LINE DESIGN DISPOSE OF THE VILLAGE CAR USINGLY SOLIDWORKS SOFTWARE: ANALISIS DISTRIBUSI KECEPATAN, TEKANAN DAN TEMPERATUR PADA PERANCANGAN SALURAN GAS BUANG MOBIL DESA DENGAN MENGGUNAKAN SOFTWARE SOLIDWORKS - Reza Prayoga (UPMI Proceeding Series, 2023)
This research aims to influence breathing activities and balance training on children's fine motor skills at Mentari Elementary School, Langkat. The type of research used is quantitative research. Quantitative research is a research method based on the philosophy of positivism, used to research certain populations or samples, collecting data using research instruments. The design used in this model is that there are two types of treatment in two experimental groups. The population in this study was 57 children at SD Mentari Langkat. The sampling technique used was purposive sampling. The sample size was 16 children at Mentar Langkat Elementary School who were divided into 3 groups randomly. The data to be analyzed needs to be tested for requirements, namely normality and homogeneity tests. The normality test is used to determine whether the data being analyzed is normal or not, the normality test uses the Shapiro-Wilk statistical test. The homogeneity test is used to determine whether the data is homogeneous or not. If the calculated sig value is greater than 0.05 then the data is normally distributed and homogeneous. However, if the calculation result is smaller than 0.05 then the data is not normally distributed and is not homogeneous. In this study, the calculation of the normality test and data homogeneity test was assisted with SPSS 16 software. Based on the research results, the average score for fine motor skills in the group that carried out breathing activities before the test (pre-test) was 6.5. After participating in breathing activities and taking the exam (post-test), the average fine motor ability score increased to 11.5. The results of statistical analysis show that the p value (P) is 0.000 (P < 0.05), which indicates a significant difference between the pre-test and post-test results of fine motor skills in the group that carried out breathing activities. Therefore, it can be concluded that breathing activities have a significant influence on improving fine motor skills.